Aahar Yojana: A perspective of Subsidised Meal Programme amid the Pandemic - Pallavi Kanungo; Apparao Thamminaina (Interdisciplinary Description of Complex Systems)
The Covid-19 pandemic left millions to suffer its impact in the forms of unemployment, displacement, acute food shortage, and more. It kept migrants and urban poor to remain more vulnerable to food. This study examined the impact of coronavirus on the food security of the urban poor through the lens of Aahar Yojana, one of the government-led subsidised meal programs in Odisha, India. It combined the interview data obtained from the Aahar centres with structured observations and evaluated interlinked elements of the institutional services and pandemic: Hunger satisfaction level, Food hygiene, Sanitation, Quality, and Quantity. Results emphasised integrating such initiatives with robust governmental interventions to shift focus from cash transfers and subsidies. The originality of this paper is that it revealed that the scope of formerly established meal programs could mitigate food insecurity as reflected from the practical benefits during the pandemic.